HRBE Diagrams and Thermoluminescence of B2O3-TeO2-Li2O-CaO Glass Doped with Lanthanide Ions - Do, Phan Van; Phi Tuyen, Vu; Xuan Ca, Nguyen (VNU Journal of Science: Mathematics - Physics; Vol 42 No 2DO - 10.25073/2588-1124/vnumap.5086, 2026)
In this study, the 40B 2 O 3 +30TeO 2 +15Li 2 O+15CaO (BTLC) glasses undoped and doped with Ln 3+ (Eu 3+ , Ce 3+ , and Tb 3+ ) ions were fabricated via the melt quenching method. Using Dorenbos’s models, the diagrams of the ground energy levels for the 4f state of the divalent and trivalent lanthanide ions within the forbidden band of the glass have been constructed based on the photoluminescence excitation spectra of Eu 3+ and Ce 3+ ions. Predictions for selecting the Ln 3+ impurities for the thermoluminescent (TL) material have been proposed through analysis of these diagrams, whereas the Ce 3+ and Ln 3+ ions were predicted to act as recombination centers. The validity of the predictions is confirmed based on the measurements of the TL glow curve and TL spectra for BTLC:Ce 3+ and BTLC:Tb 3+ samples.